2010
DOI: 10.1038/aja.2009.91
|View full text |Cite
|
Sign up to set email alerts
|

The radiation response of androgen-refractory prostate cancer cell line C4-2 derived from androgen-sensitive cell line LNCaP

Abstract: Radiation therapy is a relatively effective therapeutic method for localized prostate cancer (PCa) patients. However, radioresistance occurs in nearly 30% of patients treated with potentially curative doses. Therapeutic synergy between radiotherapy and androgen ablation treatment provides a promising strategy for improving the clinical outcome. Accordingly, the androgen deprivation-induced signaling pathway may also mediate radiosensitivity in PCa cells. The C4-2 cell line was derived from the androgen-sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The prostate cancer cell line C4-2 acquires the phenotypes of androgenindependence and osseous metastases, and it is commonly used in models of castration-resistant and aggressive prostate cancer (22). The second part of our study identified the role of Linc00963 in AI prostate cancer cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The prostate cancer cell line C4-2 acquires the phenotypes of androgenindependence and osseous metastases, and it is commonly used in models of castration-resistant and aggressive prostate cancer (22). The second part of our study identified the role of Linc00963 in AI prostate cancer cells.…”
Section: Discussionmentioning
confidence: 93%
“…Prostate cancer cell line LNCaP and C4-2 have the same genetic background and the unique advantage of remarkably mimicking the phenotypic and genotypic changes observed in clinical human PCa (22). In the current study, we used microarray technology to compare the lncRNA and mRNA expression between LNCaP cell line which was an androgen-dependent, non-metastasis (23) and the lineage-related C4-2 cell line which acquired characteristic of androgen-independence and possessed the capacity of metastasizing to lymph nodes and bone (24).…”
Section: Introductionmentioning
confidence: 99%
“…In PC3 cells, the cell cycle distribution returns to control proportions 24 h after irradiation, whereas LNCaP cells accumulate in G 1 phase. This may be explained by the inefficiency of DNA damage repair mechanisms reported in LNCaP cells in G 2 /M phase (Xie et al 2010) and consequent reliance of G 1 checkpoints, whereas PC3 cells lack the ability to arrest in G 1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…C4-2 prostate adenocarcinoma cells are derivatives from the LNCaP epithelial cell line, which lacks AnxA2 expression due to the hypermethylation of the AnxA2 promoter (65,66). They were gifts from G. N. Thalmann (University of Bern) and were maintained as reported previously (67). HPV16 pseudovirions (PsVs) encapsidating a luciferase expression plasmid were generated and purified as described previously (63,68,69).…”
mentioning
confidence: 99%